Strategi Pengembangan Objek Wisata Pantai Muara Indah Desa Ogotion Kabupaten Parigi Moutong Berdasarkan Analisis PESTEL - Nur Aulia Rahmadani; Sri Maryati; M. Iqbal Liayong Pratama (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Muara Indah Beach in Ogotion Village, Parigi Moutong Regency, has great potential for marine tourism; however, its development is still hampered by limited digital promotion, suboptimal supporting facilities, and the absence of specific regulations governing the management of the tourist area. This study aims to formulate a development strategy for Muara Indah Beach as a tourist destination based on a Political, Economic, Social, Technological, Environmental, and Legal (PESTEL) analysis. The study employs a qualitative descriptive approach using data collection techniques such as observation, interviews, and documentation involving 43 informants, including local government officials, village government officials, tourism managers, community members/MSME operators, and visitors. Data were analyzed through data reduction, triangulation, and data synthesis. The results indicate that political and social aspects serve as supporting strengths through village government support and community participation; economic aspects provide business opportunities via SMEs; environmental aspects remain pristine and constitute the main attraction; while technological and legal aspects remain constraints due to suboptimal digital promotion and the absence of specific regulations. Recommended development strategies include strengthening digital promotion, empowering SMEs, forming Tourism Awareness Groups, conserving the coastal environment, implementing digital payment systems, and gradually developing tourism management regulations to support the sustainability of Muara Indah Beach.